School policies on bullying and cyberbullying: perspectives across three Australian states. Issue 1 (2nd January 2016) - Chalmers, Caitlin; Campbell, Marilyn Anne; Spears, Barbara A; Butler, Des; Cross, Donna; Slee, Phillip; Kift, Sally
Abstract: Background: Despite decades of research, bullying in all its forms is still a significant problem within schools in Australia, as it is internationally. Anti-bullying policies and guidelines are thought to be one strategy as part of a whole school approach to reduce bullying. However, although Australian schools are required to have these policies, their effectiveness is not clear. As policies and guidelines about bullying and cyberbullying are developed within education departments, this paper explores the perspectives of those who are involved in their construction.Purpose: This study examined the perspectives of professionals involved in policy construction, across three different Australian states. The aim was to determine how their relative jurisdictions define bullying and cyberbullying, the processes for developing policy, the bullying prevention and intervention recommendations given to schools and the content considered essential in current policies.Sample: Eleven key stakeholders from three Australian states with similar education systems were invited to participate. The sample selection criteria included professionals with experience and training in education, cyber-safety and the responsibility to contribute to or make decisions which inform policy in this area for schools in their state.Design and methods: Participants were interviewed about the definitions of bullying they used in their state policy frameworks; the extent to which cyberbullying was included; and the content they considered essential for schools to include in anti-bullying policies. Data were collected through in-depth, semi-structured interviews and analysed thematically.Findings: Seven themes were identified in the data: (1) Definition of bullying and cyberbullying; (2) Existence of a policy template; (3) Policy location; (4) Adding cyberbullying; (5) Distinguishing between bullying and cyberbullying; (6) Effective policy; and (7) Policy as a prevention or intervention tool. The results were similar both across state boundaries and also across different disciplines.Conclusion: Analysis of the data suggested that, across the themes, there was some lack of information about bullying and cyberbullying. This limitation could affect the subsequent development, dissemination and sustainability of school anti-bullying policies, which have implications for the translation of research to inform better student outcomes.